Research Regarding the Vilnius University Economics Faculty - Simanauskas, Leonas (Ekonomika, 2005)
We studied the publication trends of scholarly work for the past five years in the journal Ekonomika. Every year at least four issues were published, with an average of 12,3 articles per issue. On average 1,5 authors prepared the published articles. Ekonomika is increasingly widely read, and more foreign authors are publishing in the journal. During the period of research, 14 percent of articles were written by foreign authors, while 15 percent of all authors were written by foreigners. It is noteworthy that the journal represents various scholarly and institutional interests: more than half (54 percent) of publications are written not by members of Vilnius University’s Economics faculty. The articles published by members of the Economics faculty reflect the financial details about economic conditions and development, types of markets and the development of economies and the activities of various enterprises, economic competition and so on. We analyze economic and social, financial, and accounting indicators. Statistical and infrastructural topics are analyzed along with possibilities for future research. We also begin to analyze economic theories and methodological topics.